2016
DOI: 10.1016/j.juro.2016.02.2709
|View full text |Cite
|
Sign up to set email alerts
|

Mp18-08 Focal Hifu for Treatment of Localised Prostate Cancer: A Multi-Centre Registry Experience

Abstract: INTRODUCTION AND OBJECTIVES: When focal therapy (FT) is performed with sufficient intensity to eradicate cancer, accurate evaluation for the extent of significant cancer (SC) is essential to avoid undertreatment. By D 0 Amico risk category of prostate cancer (PC), we assessed the possibility of underdiagnosis by MRI and biopsy for: 1) extra-prostatic extension (EPE) at the ablation field; and 2) SC left in untreated area. We then verified the applicability of quadrant-based regional FT to intermediate-and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Our primary outcome was failure free survival (FFS), defined as transition to radical, wholegland or systemic therapy as well as metastases/death as used in our previous reports of focal therapy (definition 1) (10,11). This is also the primary endpoint used in the PART randomised control trial (RCT) comparing focal with radical therapy (12).…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Our primary outcome was failure free survival (FFS), defined as transition to radical, wholegland or systemic therapy as well as metastases/death as used in our previous reports of focal therapy (definition 1) (10,11). This is also the primary endpoint used in the PART randomised control trial (RCT) comparing focal with radical therapy (12).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Taimur T. Shah [1,2,3], Max Peters [4], David Eldred-Evans [1], Saiful Miah [1,2,3], Tet Yap [5], Nicholas A. Faure-Walker [5], Feargus Hosking-Jervis [1], Benjamin Thomas [3], Tim Dudderidge [6], Richard G. Hindley [7], Stuart McCracken [8], Damian Greene [9], Raj Nigam [12], Massimo Valerio [10], Suks Minhas [2], Mathias Winkler [1,2], Manit Arya* [1,2,3,11], Hashim U. Ahmed* [1,2] Introduction Currently, patients with non-metastatic clinically significant localised prostate cancer are offered either radical prostatectomy or radiotherapy. Both interventions have robust longterm cancer control outcomes but due to targeting the entire prostate confer significant negative effects on genitourinary function, particularly with regards to incontinence, urinary symptoms, erectile function and rectal side-effects (radiotherapy) (EF) (1,2).…”
mentioning
confidence: 99%
“…HIFU ablation causes coagulation necrosis in the targeted tissue by generation of a cavitation effect, and it is a good alternative in the management of moderately and well-differentiated localized prostate cancer and of local recurrence after EBRT (26). A recent multicenter study in the United Kingdom showed that a preponderance of treated patients (81%) were of intermediate risk, followed by low risk (13%), and high risk (6%), showing a wide range of use cases (27). Transurethral high-intensity US, a variant of HIFU, is less focused, delivering whole-gland ablation.…”
Section: Hifu Ablationmentioning
confidence: 99%